Experiences of intimate relationships in young men who sexually offended during adolescence: interviews 10 years later. Issue 3 (1st September 2016) - Ingevaldson, Sara; Goulding, Anneli; Tidefors, Inga
ABSTRACT: Intimate relationships and sexuality are important, but often complicated, aspects of life. In this study we examined experiences of intimate relationships and sexuality in 20 young men, aged 22–31 years, who had sexually offended during adolescence. The participants were interviewed and the transcripts were thematically analysed. The main picture observed was that of young men with unfulfilled needs and a low capacity to meet those needs. Additionally, the men's experiences of intimate relationships and sexuality seemed to be affected by their experience of having sexually offended. Some men longed for closeness with a partner but were afraid of getting too close. Others distanced themselves from relationships, claiming that they did not need others. These findings may demonstrate the men's self-protective strategies for handling their identification as sexual offenders. These 20 men could also have been struggling with universal questions about closeness and sexuality while bearing other burdens, such as mistrust in others and feelings of shame, that interfered with this struggle.